Global Report on Islamic Finance : Islamic Finance - A Catalyst for Shared Prosperity? - World Bank (Washington, DC: World Bank, 2016)
Income inequality has increased considerably in the aftermath of the financial crisis of 2007–08 to the extent that one percent of global population possess almost half of the global assets. Whereas the development community is unanimous to tackle growing inequality and imbalance in the distribution of wealth, there is a difference of opinion as to the approaches to achieve this goal. This report presents a perspective from Islamic finance on how shared prosperity can be enhanced.